Establishing Fair Publishing Modes For The African Scholarly Community - Havemann, Jo (My University, 2023)
Lightening Talk held at the JISC Online Workshop: Exploring the potential of alternative publishing models on Jan 19, 2023. Slides also available online at https://docs.google.com/presentation/d/15LmNK_GZE624sbVrdVOqjn8_XpjliPlMlBVhCQ5P-Zc/edit?usp=sharing
Keywords: Persistent identifier; Open Access; Global Equity